CLINICAL UTILITY OF KIDNEY FAILURE RISK EQUATION IN DIABETES AND CHRONIC KIDNEY DISEASE - Ooi, Ying Guat; Sarvanandan, Tharsini; Hee, Nicholas Ken Yoong; Lim, Quan Hziung; Beh, Hooi Chin; Rozi, Nur Raziana; Selvaraj, Christine Shamala; Abdullah, Adina; Adnan, Wan Ahmad Hafiz Wan Md; Paramasivam, Sharmila S; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Heterogeneity in disease course and prognosis makes managing CKD difficult. An accurate risk stratification algorithm is crucial to predict CKD progression to ESKD for individualized management. The Kidney Failure Risk Equation (KFRE), developed in 2011, is the most widely validated prediction model for 2- and 5-year ESKD progression risk across multiple underlying etiologies with potential for clinical utility. METHODOLOGY This study aims to investigate if KFRE risk scores differ significantly among individuals with or without diabetes. We conducted a retrospective study on adults with CKD (eGFR 15-59 ml/min/1.73 m2 ) who attended our hospital outpatient follow-up from January to December 2022 with available data for calculation of 4-variable KFREs [age, sex, eGFR, urine albumin-creatinine ratio (uACR)]. Two-sample t-test and Mann-Whitney U test were performed to analyse the difference between the two groups. RESULTS Out of 10,391 adults with CKD, 1,823 that fulfilled the inclusion criteria were analysed, with a mean age of 70 years, 52% were male, mean eGFR of 45ml/min/1.73 m2 and median uACR of 8.4 mg/mmol. Majority (84%) have diabetes with a mean HbA1c of 7.8%. Individuals with CKD and diabetes had lower eGFR, heavier albuminuria and had younger age than those without diabetes (p <0.001). These findings further translate to statistically significant higher KFRE risk scores for individuals with diabetes. For those with eGFR between 30-59 ml/min/1.73 m2 , 9.4% of individuals without diabetes and 14.8% of those with diabetes met the referral criteria for nephrology care when setting a KFRE score threshold of more than 5% over 5 years. CONCLUSION The lack of uACR monitoring resulted in a smaller sample size than anticipated. We advocate all healthcare professionals to monitor uACR and utilize the KFRE score in clinical practice when managing CKD or diabetes with eGFR between 15-60 ml/min/1.73 m2 to guide referral to multi-disciplinary care and raise public awareness about the risk of ESKD.